PELANGGARAN HUKUM OLEH KOMISI PEMILIHAN UMUM SUMATERA BARAT DALAM PEMILIHAN UMUM CALON ANGGOTA DEWAN PERWAKILAN DAERAH TAHUN 2024: Violations of the Law by the West Sumatra General Election Commission in the 2024 General Election of Regional Representative Council Candidates - Stefania Apriliani Armaya; Ferry Edwar (Reformasi Hukum Trisakti, 2025)
General elections are the primary means of upholding citizens' political rights in Indonesia's democratic system. This paper examines administrative violations committed by the West Sumatra General Elections Commission (KPU) in the 2024 Regional Representative Council (DPD) Election. The problem formulation analyzed includes the forms of administrative violations by the KPU and their impact on legal certainty and the protection of political rights of election participants. The research uses a normative legal method with a legal principles approach, where data is collected through document studies and analyzed qualitatively using deductive techniques. The results show that the KPU's action in not including Irman Gusman in the DCT constitutes a violation of the code of ethics and election administration, which is then exacerbated by non-compliance with the PTUN decision ordering the restoration of Irman Gusman's rights. The discussion highlights how these violations create legal uncertainty, undermine public trust, and threaten election integrity. In conclusion, administrative violations by the West Sumatra KPU have violated the principles of justice and the rule of law, thus requiring strict sanctions to ensure that elections are fair, transparent, and respect the constitutional rights of every citizen.